Law Enforcement Actions Against Investment Fraud Committed Via WhatsApp (WA) at the Cirebon City Police Department - Ilham; Sanusi; Siska Karina (Eduvest - Journal of Universal Studies, 2026)
This study discusses law enforcement actions against investment fraud committed via WhatsApp (WA) at the Cirebon City Police Department. This study employed a normative juridical approach with a qualitative descriptive method, namely by analyzing applicable laws and regulations, supported by data from interviews and field studies. The results of the study indicate that the perpetrators committed fraud by offering investments through a fundraising system, promising quick profits, using false identities, and employing persuasive communication to convince victims. Law enforcement against this crime was carried out in accordance with procedures through the investigation and inquiry stages based on Article 492 of the Criminal Code and the Information and Electronic Transactions Law. However, in practice, several obstacles remained, such as difficulties in tracking the perpetrators, the use of third-party accounts, and limited access to digital data. This study recommends increasing the capacity of law enforcement officers, updating regulations, and combining preventive and repressive approaches in the community as important steps to improve the effectiveness of law enforcement in the digital era.